A MEDICALIZAÇÃO INFANTIL NA VIDA ESCOLAR - Luiza Barcelos Ribeiro, Ana; Gomes da Silva Amaral Lessa, Thamires; Pires André, Bianka (LINKSCIENCEPLACE, 2026)
The medical medicalization of children is a phenomenon that has attracted the attention of many professionals in the area of health and education, this fact has been the result of an immediate society in which we are inserted, where the problems that are not medical but social are approached as if they were diseases or disorders, without highlighting the need to consider human diversity, their differences and specificities. In this context other alternatives are not observed for the treatment of this diversity, considering only as a medical issue and that often needs to be medicated. This work, based on a bibliographical review, seeks to reflect on the causes of child medicalization and how it has been developed in the educational environment, using current and renowned authors in the area. We will start from its concept and the differentiation of this concept from that of medication, we observe that medicalization is a social issue and consequently affects the child, we base the content with questions related to the increase of diagnoses in childhood. It arises in the lives of children in the educational environment as a way to heal the learning problems that affect many of them. These problems, seen as individual illnesses, begin to be treated through medications that promise to assist the child in developing his learning and behavior. Specifically in relation to medicalization of the life of children and adolescents, there is the articulation with the medicalization of education in the invention of the diseases of not learning and the medicalization of behavior.